Certain Remarks on the Element of Will in Customary International Law: A Short Comment - Kałduński, Marcin (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The article examines the element of will in customary international law. This brief comment is not intended to address all of the important issues that arise with respect to the formation and binding force of customary international law. It will only invite attention to a question concerning the element of the will of States. Thus, the aim of this comment is to stimulate the reader to consider the nature and essence of the will of States in customary international law.
Keywords: element of will; customary law; binding force